IMPLEMENTASI APLIKASI “SIAS / SISTEM INFORMASI AKUNTANSI SEKOLAH” DALAM PENYUSUNAN LAPORAN KEUANGAN SEKOLAH MUHAMMADIYAH DI KABUPATEN BOJONEGORO - Syaiful, Syaiful; Anugrah, Indra Gita; Aufa, Muhammad; Tumirin, Tumirin; Suwarno, Suwarno (Universitas Muhammadiyah Gresik, 2024)
Community service activities aim to provide understanding and skills for the Muhammadiyah School Treasurer in Bojonegoro Regency regarding the preparation of financial reports using the